High Number and Specific Comorbidities Could Impact the Immune Response in COVID-19 Patients - Liu, Dafeng; Yuan, Xiaoyan; Gao, Fengjiao; Zhao, Bennan; Ding, Ling; Huan, Mingchang; Liu, Chao; Jiang, Liangshuang (Frontiers in Immunology, 2022)
Background— Cellular immunodeficiency and comorbidities are common in COVID-19 patients. Aim—In this study, we aimed to study the impact of comorbidities on the cellular immunity in COVID-19 patients. Methods— A total of 55 healthy controls and 718 COVID-19 patients were divided into subgroups based on the number and types of comorbidities present. Baseline peripheral lymphocyte and subsets were compared between the control group and the groups with comorbidities based on the different amount of and types of comorbidities, and the relationship between the lymphocyte counts and subsets with the number and types of comorbidities was investigated. Results— Compared with the control group, the lymphocyte counts and T cell subsets were significantly increased in the groups with comorbidities, but both B and NK cell subsets were significantly decreased in the no comorbidity group and in most of the groups with comorbidities (all P<0.05). Moreover, compared with the no comorbidity group, in the most comorbidities groups, the lymphocyte percentages and CD19+ and CD56+ counts were significantly decreased (all P<0.05). In the three comorbidities group, the lymphocyte counts and T cell subsets were all significantly decreased, but the CD56+ percentage was obviously increased (all P<0.05). The number of comorbidities was negatively correlated with the lymphocyte counts and the T and NK cell subsets. A negative correlation also existed between cancer and both the lymphocyte counts and the T cell subsets, between chronic hepatitis B and the lymphocyte counts, and between chronic kidney disease and the CD3+ counts. A positive correlation existed between nonalcoholic fatty liver (NAFLD) disease and both lymphocyte and CD3+ counts. The risk factors were number of comorbidities for the lymphocyte count, CD3+CD4+ and CD3+CD8+ percentages, NAFLD for the lymphocyte and CD3+ counts, cardiovascular diseases for CD3+CD4+ and CD3+CD8+ percentages, diabetes mellitus for the CD3+CD8+ percentage, and cancer for the CD3+ percentage, respectively. Conclusions—High numbers of comorbidities and specific comorbidities could impact the immune response of COVID-19 patients. This study provides a reference for clinicians in the identification of suitable and timely immunotherapy for COVID-19 patients.